The Roots of Conflicts between Muslims and Christians in Indonesia in 1995–1997. (July 2020) - Sukamto, Amos; Pramono, Rudy
This article discusses the roots of the Islam–Christianity conflict in the mid-1990s in Indonesia. The analysis showed that this conflict was motivated by various factors such as a feeling of dissatisfaction among Muslims, the problem of christianization that was happening not only in the community but also entered the bureaucracy and military, the emergence of various government policies and MUI fatwas, which added fuel to the already strained relations between the two religions and finally the economic disparity in which Christians were seen as people who were rich and enjoyed the fruits of the development. In the mid-1990s when detention factors, namely the authorities and the military, began to weaken, the conflict escalated to a massive scale.